PEMANFAATAN PERPUSTAKAAN SEBAGAI SUMBER BELAJAR GEOGRAFI SISWA KELAS XI DI SMA GIRIAN TOMOHON - Bologi, Krisda; Oroh, Hilda Vemy; Rifani, Irfan; Ramadhan, Muhamad Isa; Putri, Anindya Puspita; Selfiardy, Syafrida (Fakultas Ilmu Sosial dan Hukum, 2025)
This research aims to find out whether using the library as a learning resource interest in learning to find out the role of teachers in motivating students to use the library as a learning resource for class XI IPS students at Tumou Tou Girian Bitung Christian High School The research method used is descriptive qualitative with interview observation and documentation data collection techniques The research results prove that libraries are part of an effective learning resource it can be seen from students feeling happy when studying in the library because it is easy to get information and complate assignments The library provides many reference books that help students learn more quickly and easily This explains that using the library as a learning resource can increase students interest in learning Teachhers combine classroom learning which means teachers often create lessons that are not only centered in the classroom but can also direct students to do direct learning in the library < em>< p>